TURKISH PERCEPTION OF THE MEDITERRANEAN AND EURO-MEDITERRANEAN RELATIONS IN THE 1980s - (:unkn) unknown (MEDITERRANEAN INST UNIV MALTA, 2015)
The article aims to inquire into Turkey's regional perception of the Mediterranean as an ideational and security input in its foreign relations in the 1980s. Turkey's ideational and strategic perceptions of the Mediterranean do not necessarily exclude each other, but the country has failed to create a coherent foreign policy identity. This paper will focus on the 1980s in order to show how the Europeanization of the Mediterranean side-lined Turkey's linkage with the Mediterranean and reaffirmed Turkey's hard security-led view of the region at the expense of the rising multidimensional security outlook. Turkey's ambiguous 'we-ness' with regard to the Mediterranean became more obscure with the accession of Greece (1981), Spain, and Portugal (1986) to the European Community (EC), and Turkish strategic concerns continued to be the priority despite the commencement of the EC's timid steps to construct a collective Mediterranean identity. The paper does not regard Turkey's identification with the Mediterranean as an end in itself but inquires into it as a causal factor in Turkish foreign policy towards the region. More to the point, in view of some tremendous changes taking place in the international relations of the Mediterranean, the article aims to draw attention to ideational and tangible sources of Turkey's Mediterranean policy in retrospect.